Islamic Approach to Violations against the Sanctity of the Deceased: A Case Study on Necrophilia in Islam - Fuadi Isnawan (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
This article investigates the legal implications of necrophilia within the framework of Islamic law, specifically addressing whether such acts can be categorized as zinā ‘adultery’. The primary aim of this research is to analyze how Islamic teachings interpret and regulate sexual relations with deceased individuals, with a focus on the fundamental principles of human dignity and sanctity. Utilizing a qualitative method alongside a case study approach, this study involves a comprehensive review of Islamic texts, legal cases, and scholarly interpretations. The data sources encompass Islamic literature, the Qur'an, Hadith, and legal references, including scientific journals and academic books. The theoretical framework is anchored in the concepts of maqāşid syarī’ah, particularly the preservation of religion ‘ḥifẓ al-dīn’, intellect ‘ḥifẓ al-aql’, and life ‘ḥifẓ al-nafs’. The findings indicate that necrophilia is regarded as a serious violation under Islamic law, representing a breach of both moral and legal standards, which results in stringent penalties. In conclusion, this study underscores the importance of upholding the dignity of the human body after death, as mandated by Islamic law. This research contributes by clarifying how Islamic law addresses necrophilia and reinforcing societal norms related to the sanctity of life and death.